2018
DOI: 10.1080/09644016.2018.1488484
|View full text |Cite
|
Sign up to set email alerts
|

The green state and industrial decarbonisation

Abstract: The large share of carbon emitted by energy-intensive industries in the extraction and processing of basic materials must be limited to decarbonise society and the economy. Ways in which the state can govern industrial decarbonisation and contributes to green state theory are explored by addressing a largely ignored issue: the green state's industrial relations and its role in industrial governance. With insights from a Swedish case study, the tension between the state's economic imperative and ecological conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…I draw on this history and see-joining Gough [44] (p. 145)-that the policy idea of a virtuous circle of sustainable welfare favors "an active interventionist 'innovative' state, with substantial public investment and greater regulation and planning". The "green state" plays a pivotal role in decarbonizing economy [57] and facilitating the degrowth transformation [15,51]. As Koch has shown, state-led ecosocial policies can overcome the imperative of economic growth if they are "integrated into comprehensive strategy" [46] (p. 13).…”
Section: Towards the Virtuous Circle Of Sustainable Welfarementioning
confidence: 99%
“…I draw on this history and see-joining Gough [44] (p. 145)-that the policy idea of a virtuous circle of sustainable welfare favors "an active interventionist 'innovative' state, with substantial public investment and greater regulation and planning". The "green state" plays a pivotal role in decarbonizing economy [57] and facilitating the degrowth transformation [15,51]. As Koch has shown, state-led ecosocial policies can overcome the imperative of economic growth if they are "integrated into comprehensive strategy" [46] (p. 13).…”
Section: Towards the Virtuous Circle Of Sustainable Welfarementioning
confidence: 99%
“…Relating to theories developed by Levin et al [17], Hildingsson and Khan [70] found support for a gradually more progressive approach to policy change in the case of the Swedish energy transition. Taking a wider governance perspective, and with Sweden as an example, Hildingsson, Kronsell and Khan [71] analysed the role of the state in governing the decarbonisation of ENRIs, while Kronsell, Khan and Hildingsson [72] studied actor relations in climate policy making. They find that the tension between the state's economic imperative and ecological concerns in greening industry are shown to persist.…”
Section: Main Thematic Contributionmentioning
confidence: 99%
“…This could include agency-oriented and structural (institutional, discursive, normative) explanations as well as understanding mechanisms that might trigger change and create room for policy change. Other studies focus on the role of the state in relation to other actors and explore the governance conditions for employing decarbonisation strategies (e.g., [71]).…”
Section: Governance Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition theory suggests that we pay attention to if and how innovative niche actors are included in the climate policymaking process as well as to the role of dominant regime actors. Transition scholars have mainly analysed incumbent regimes in terms of their strategies to resist change (Geels, ; Markard et al, ) although some have developed a more nuanced view on the role of incumbents showing how they can both obstruct transitions by capturing transition processes to align them with their own interests and support sustainability innovations (see, eg, Hildingsson, Kronsell, & Khan, ; Smink, ; Späth, Rohracher, & von Radecki, ). This points to the need to consider the potential of incumbent regime actors to act as change agents and what dilemmas and challenges this might entail.…”
Section: Theoretical Perspectives On Actor Relations In Climate Policmentioning
confidence: 99%